Suppression of chaos in a multicomponent chemical reaction via Optimal Linear Control∗ - Faria, Henrique A.M. [UNESP]; Chavarette, Fábio R. [UNESP] (Sociedade Paranaense de Matemática, 2025)
In this study, we address the problem of controlling chaotic behavior in chemical reactions involving four components occurring in a continuously stirred tank reactor. The controller developed in this study is based on the theory of optimal linear control, proposing a function to maximize the chemical reaction rate and suppress the chaotic behavior in the system. The numerical experiments performed demonstrated the ability to stabilize the chaotic behavior of the chemical reactions in this four-variable system. The chaotic oscillatory motion of the mass concentrations in the multicomponent system was driven towards a stable point. The control technique proved to be efficient for this problem and has the potential for application in chemical reactions involving multiple components.
Keywords: chaos suppression; chemical reactions; Optimal linear control